Entrance to the Chinese Kwan Kung Temple - Mumbai Archive Project Team (Jio Institute, 2024)
In the 1850s, Chinese immigrants began to arrive in Mumbai. These Chinese immigrants originated in the southern Chinese port city of Canton and were residents of the See Yup Koon neighbourhood. The majority of them were sailors who worked on ships that travelled between China and India. Chinatown was founded in Mazagon around the beginning of the 20th century. A remnant of the Chinatown is Kwan Kung Temple, a Chinese temple, located at 12 Nawab Tank Road.